Effects of Repeated Caesarean Sections on Maternal and Fetal Outcomes - Maha Shinshin; Noura Elawam (AlQalam Journal of Medical and Applied Sciences, 2025)
The occurrence of birth via cesarean section has become a prevalent intervention in contemporary obstetric practice. Presently, patients with a prior cesarean section constitute a significant proportion of the obstetric population. Furthermore, the incidence of both primary and repeat cesarean deliveries is experiencing an upward trend globally. The objective of this investigation is to evaluate the outcomes associated with repeat cesarean sections in women with a history of one or more previous cesarean deliveries, and to compare these outcomes concerning maternal and neonatal morbidity and mortality. This study employed a retrospective case series design, conducted within the Department of Obstetrics and Gynecology at the University Hospital, spanning from July 2023 to June 2024. A total of 500 pregnant women who underwent cesarean sections due to a history of one or more prior cesarean deliveries were systematically assessed and analyzed. The average age of the subjects was determined to be 32.17 years, accompanied by a standard deviation of 4.5. Approximately 63.6% of the subjects experienced multiple cesarean sections (C/S), while the remaining 36.4% underwent a single C/S. Antepartum complication observed included placenta previa (3.2%), premature rupture of membranes (13%), uterine rupture (2.6%), and other complications (13%). Postoperative complications identified within this investigation included; 5.6% experiencing postpartum hemorrhage (PPH), 1% developing deep vein thrombosis (DVT), 3.3% suffering from wound infections, 16.6% enduring prolonged hospital stays, and 3.6% encountering various other complications. The incidence of preterm infants was recorded at 5.6%. Respiratory distress syndrome (RDS) was noted in 19.6% of the neonates. Neonatal mortality was reported in ten cases (2%), alongside intrauterine fetal demise (IUFD) in eight cases (1.6%). This study showed that the risk of maternal morbidity and mortality rises in tandem with the number of cesarean sections performed. This relationship is still debatable even though the study found no correlation between the number of cesarean sections and newborn morbidity and mortality. أصبح حدوث الولادة عن طريق العملية القيصرية تدخلاً شائعًا في ممارسة التوليد المعاصرة. في الوقت الحاضر، يشكل المرضى الذين خضعوا لعملية قيصرية سابقة نسبة كبيرة من سكان التوليد. علاوة على ذلك، يشهد معدل حدوث الولادات القيصرية الأولية والمتكررة اتجاهًا تصاعديًا على مستوى العالم. الهدف من هذا البحث هو تقييم النتائج المرتبطة بالولادات القيصرية المتكررة لدى النساء اللاتي لديهن تاريخ من ولادة قيصرية واحدة أو أكثر سابقة، ومقارنة هذه النتائج فيما يتعلق بالمرض والوفيات لدى الأمهات والأطفال حديثي الولادة. استخدمت هذه الدراسة تصميم سلسلة حالات بأثر رجعي، أجريت داخل قسم التوليد وأمراض النساء في المستشفى الجامعي، في الفترة من يوليو 2023 إلى يونيو 2024. تم تقييم وتحليل ما مجموعه 500 امرأة حامل خضعن لعمليات قيصرية بسبب تاريخ من ولادة قيصرية واحدة أو أكثر سابقة بشكل منهجي. تم تحديد متوسط عمر الخاضعات ليكون 32.17 عامًا، مصحوبًا بانحراف معياري قدره 4.5. حوالي 63.6% من النساء خضعن لعمليات قيصرية متعددة، بينما خضعت النسبة المتبقية (36.4%) لعملية قيصرية واحدة. وشملت المضاعفات التي لوحظت قبل الولادة المشيمة المنزاحة (3.2%)، وتمزق الأغشية قبل الأوان (13%)، وتمزق الرحم (2.6%)، ومضاعفات أخرى (13%). وشملت المضاعفات التي تم تحديدها بعد الجراحة في هذا البحث؛ تعرض 5.6% لنزيف ما بعد الولادة (PPH)، وتطورت لدى 1% خثار الأوردة العميقة (DVT)، وتعرضت 3.3% لالتهابات الجروح، وتحملت 16.6% فترات إقامة طويلة في المستشفى، وواجهت 3.6% مضاعفات أخرى مختلفة. تم تسجيل حدوث الأطفال الخدج بنسبة 5.6%. ولوحظت متلازمة الضائقة التنفسية (RDS) لدى 19.6% من الأطفال حديثي الولادة. تم الإبلاغ عن وفيات الأطفال حديثي الولادة في عشر حالات (2٪)، إلى جانب وفاة الجنين داخل الرحم (IUFD) في ثماني حالات (1.6٪). أظهرت هذه الدراسة أن خطر الإصابة بالأمراض والوفيات لدى الأمهات يرتفع بالتوازي مع عدد عمليات الولادة القيصرية التي يتم إجراؤها. لا تزال هذه العلاقة قابلة للنقاش على الرغم من أن الدراسة لم تجد أي ارتباط بين عدد عمليات الولادة القيصرية والإصابة بالأمراض والوفيات لدى الأطفال حديثي الولادة